1999
DOI: 10.1034/j.1600-051x.1999.260601.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory animal models in periodontology

Abstract: Animal models are needed to objectively evaluate the pathogenesis of human periodontal diseases and its various treatment modalities. Selection of the appropriate animal model depends on the similarity of the periodontium and the nature of the disease to that of humans. The more commonly used animal models for studying the pathogenesis of periodontal disease, use of implants and guided tissue regeneration have been dogs and nonhuman primates. Periodontal disease in rodents has not been found to be as closely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
97
0
11

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 35 publications
1
97
0
11
Order By: Relevance
“…However, more recent studies on humans have shown no relation between periodontal disease and alcohol consumption [6][7] . The use of rat models has been applied in the evaluation of periodontal pathogenesis 8 and regarding the influence of risk indicator/factors, such as estrogen deficiency [9][10] , alcohol consumption [11][12][13][14][15][16] , nicotine 17 and simultaneous nicotine and alcohol use 18 on disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent studies on humans have shown no relation between periodontal disease and alcohol consumption [6][7] . The use of rat models has been applied in the evaluation of periodontal pathogenesis 8 and regarding the influence of risk indicator/factors, such as estrogen deficiency [9][10] , alcohol consumption [11][12][13][14][15][16] , nicotine 17 and simultaneous nicotine and alcohol use 18 on disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Although many previous workers have also investigated the cultivable oral microbiota of dogs, most have relied upon conventional identification methods, and their studies have been aimed at gaining a better understanding of the human microbiota. In particular, the dog has often been used as an animal model for human oral diseases, such as periodontal disease (28), and it has also received attention because of the bacteria that it may transfer to people, for example, through bites (1,9). In this respect it has been recognized that the dog has a distinct oral microbiota, as it is widely believed that bites from dogs are less dangerous than human bites in terms of wound infection potential (12).…”
mentioning
confidence: 99%
“…However, the rate of proliferation differed among the animals, so that epithelial downgrowth sometimes stopped at the coronal level of the notch, and sometimes extended beyond it. In general, the gingival tissue of rats shows features similar to those in man (20,25,26), and for this reason rats have often been used in studies of periodontal disease (20,22,23,27,28). Several previous studies that have assessed the effects of EDTA gel as a coadjuvant in periodontal treatment focused on the root surface of human teeth extracted due to severe periodontitis.…”
Section: Discussionmentioning
confidence: 99%